Investigation of the Asymmetric Features of X-Rudder Underwater Vehicle Vertical Maneuvring and Novel Motion Prediction Technology - Yinghua Li; Ziying Pan; Yongcheng Li; Changyou Song; Minghui Zhang; Mengchen Ren (Journal of Marine Science and Engineering)
An X-rudder underwater vehicle’s hydrodynamic force acting on its rudder will display asymmetrical characteristics during vertical movement that are absent from a cross-rudder vehicle. This paper presents a novel hydrodynamic expression method based on rotational hydrodynamic transformation through a detailed analysis of the local flow characteristics around the tail attachment during the vertical plane maneuvering of the X-rudder vehicle, given that the conventional Taylor expansion-based hydrodynamic expression method is unable to characterize this asymmetric characteristic. With the help of this technique, a novel expression that can precisely describe the asymmetric hydrodynamic properties during the X-rudder vehicle’s underwater vertical plane maneuvering is created. This paper next concentrates on common vertical plane maneuvering motion situations and performs simulation predictions using both new and conventional expressions based on Taylor expansion. The asymmetric characteristics of the X-rudder underwater vehicle in vertical plane maneuvering have been experimentally confirmed, and the asymmetric characteristics become more pronounced as the speed increases, according to the results, which are compared with those of tests using self-driving models. Overall, the new model accurately describes the asymmetric features of the X-rudder vehicle’s vertical maneuvering motion and correlates well with the experimental findings.